How does the joint dermatology–rheumatology clinic benefit both patients and dermatologists?. Issue 3 (3rd March 2020) - Theodorakopoulou, Elina; Dalamaga, Maria; Katsimbri, Pelagia; Boumpas, Dimitrios T.; Papadavid, Evangelia
Abstract: Psoriasis (Pso) and psoriatic arthritis (PsA) are chronic and debilitating diseases which often develop in the same patient and are linked to a wide range of comorbid conditions. Dermatologists and rheumatologists need to cooperate in combined clinics, especially when they deal with severe, recalcitrant disease, and multiple comorbidities. The clinical and research benefits of this collaboration have been previously described to contribute to a better and more sustainable health care system. To apply a more holistic approach of patients with Pso and PsA, we established the first dual care clinic in Greece, for Pso and PsA patients, based at Attikon General University Hospital. Hereby, we describe the infrastructure and operation of a combined Pso and PsA clinic (PPAC), in the national health care system of Greece, and its impact on the management of Pso and PsA. The PPAC is a single‐day joint clinic, held once a week, which consists of three dermatologists and three rheumatologists. We present the results of 185 newly diagnosed patients between December 2018 and January 2019. Mean age of onset of Pso was 34 ± 16 years old and 47 ± 12 years old for PsA. Most patients suffered from severe plaque Pso (144/185, 78%) and asymmetric oligoarticular arthritis (59/185, 32%), for which they were receiving treatment with biologic agents (105/185, 57%). Many required monitoring for hypertension (74/185, 40%), dyslipidemia (69/185, 37%), diabetes (17/185, 9%), and depression (20/185, 11%). Patients reported high levels of care satisfaction (visual analogue scale: 86 ± 11.5), using the PPAC facility, compared to different referrals between specialties. This is the first joint dermatology–rheumatology clinic in Greece, providing comprehensive care in patients with Pso and PsA. Our results support the concept of combined clinics delivering better integrated care for such patients.